2022
DOI: 10.1371/journal.pone.0269992
|View full text |Cite
|
Sign up to set email alerts
|

Some bee-pollinated plants provide nutritionally incomplete pollen amino acid resources to their pollinators

Abstract: For pollinators such as bees, nectar mainly provides carbohydrates and pollen provides proteins, amino acids, and lipids to cover their nutritional needs. Here, to examine differences in pollinator resources, we compared the amino acid profiles and total amino acid contents of pollen from 32 common entomophilous plants in seven families. Our results showed that the amino acid profiles and contents in pollen samples differed according to the plant family and the chromatography method used, i.e., high-performanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(31 citation statements)
references
References 55 publications
0
25
0
Order By: Relevance
“…resulted in failure to lay eggs in B. terrestris micro‐colonies; while Austin and Gilbert (2021) found Osmia bicornis larvae survival was positively correlated with carbohydrate quantity. Therefore, bee species benefit from a diverse diet in which pollen and nectar are sourced from a variety of plant species in order to obtain all essential amino acids and sufficient quantities of sugar nectar (Hanley et al, 2008; Jeannerod et al, 2022; Vaudo et al, 2015). Although our novel WB mix was found to attract the greatest abundance of insect pollinators, we did not record if visits were made for pollen or nectar foraging/collection.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…resulted in failure to lay eggs in B. terrestris micro‐colonies; while Austin and Gilbert (2021) found Osmia bicornis larvae survival was positively correlated with carbohydrate quantity. Therefore, bee species benefit from a diverse diet in which pollen and nectar are sourced from a variety of plant species in order to obtain all essential amino acids and sufficient quantities of sugar nectar (Hanley et al, 2008; Jeannerod et al, 2022; Vaudo et al, 2015). Although our novel WB mix was found to attract the greatest abundance of insect pollinators, we did not record if visits were made for pollen or nectar foraging/collection.…”
Section: Discussionmentioning
confidence: 99%
“…showed the Fabaceae mix was statistically no better than a fallow plot for attracting bumblebees (though see Cole et al, 2022 The nutritional components of pollen and nectar varies widely between plant species and families (Hanley et al, 2008;Jeannerod et al, 2022), which can in turn limit the growth and survival of bee broods. Brunner et al (2014) found that a diet consisting of just Taraxacum spp.…”
Section: Treatment Effect On Visitationsmentioning
confidence: 99%
See 2 more Smart Citations
“…Although nectar sugar content was not measured, larger floral display area is often correlated to nectar sugar content (Guezen & Forrest, 2021), suggesting that bees were attracted to visual traits that signal nectar quality rather than pollen protein concentration. In addition, the relative composition of amino acids in pollen can vary substantially among flowering plants (Jeannerod et al, 2022; Nepi et al, 2012), though the consequences of this variation for bee foraging are not yet entirely clear. In honeybees ( Apis mellifera L.) foraging is linked with the proportion of essential amino acids (valine, leucine and isoleucine) in pollen and can drive preferences for certain plant species (Cook et al, 2003), but wild bee nutritional networks are reported to exhibit little specialisation for specific amino acids (Kriesell et al, 2017).…”
Section: Discussionmentioning
confidence: 99%